An automatic target shooter using arduino - Yaacob, Fatimah Azzahra (2025)
The project aims to develop an Automatic Electronic Target Shooter, addressing limitations in existing products by introducing dynamic targets with horizontal movement, laser sensors for improved accuracy, and real-time scoring display. These enhancements cater to individual needs for challenge, precision, and feedback, providing a more engaging and fulfilling targeting experience. Additionally, the project has broader community and global significance, promoting physical activity, sustainability, and skill development. The project includes a functioning prototype with static and moving targets, accurate target detection using Arduino circuits, and a scoring display feature. Moreover, utilizes programming skills to ensure smooth operation of the system. Overall, this project represents a significant advancement in interactive target systems, with potential applications in entertainment, training simulations, and education.